Biochemical and electrophysiological responses in goats subjected to transportation, lairage, and slaughter - Othman, Azalea Hani (2020)
Food animal production involves routine husbandry procedures including handling, transportation, introduction to novel environments, and eventually slaughter. These activitiesincur stress and pain to the animals. Pre-slaughter management of these animals could impact the experience of pain at slaughter. Therefore, this study was conducted to determine the effects of stressors in routine livestock management, by the changes in haematological parameters, serum biochemical, stress hormone, electroencephalogram (EEG), and neuro-histological findings, in goats subjected to 1-, 2-, and 6-h road transportation, pre-slaughter 3-, 6-, and 16-h lairage, and slaughter. Goats exposed to 1-h road transportation showed higher neutrophil to lymphocyte ratio (N:L), neutrophil counts, plasma cortisol concentrations (CORT), and serum creatine kinase (CK) at post-transportation and post-slaughter than at pre-transportation (baseline) period. Serum alanine aminotransferase (ALT) and aspartate aminotransferase (AST), plasma protein (PP) and hematocrit (PCV) did not vary from baseline. The EEG median frequency (F50) was significantly higher (p<0.05) at pre-slaughter than baseline suggesting increased arousal state, and remained high at post-slaughter period. It is suggested that the stress of handling, novel environment, and transportation increased slaughter pain threshold in goats through stress-induced analgesia (SIA) mechanism. Goats transported for 2 (T2) and 6 h (T6) showed significantly higher (p<0.05) neutrophil counts, serum CK and ALT concentrations than those at pre-transportation period. Based on the high CORT, goats of both transportation groups were already stressed prior to transportation. However, CORT value decreased and EEG unchanged after transportation, which could be attributed to adaptation of goats to the transportation conditions. Increased PCV and PP were also observed in the T6 goats, indicating dehydration. The T2 and T6 goats were subjected to lairage for either 3 (L3), 6 (L6) or 16 (L16) h before slaughter. Among treatment groups, the pre-slaughter F50 was highest in the goats subjected to 2-h transportation and 3-h lairage. The F50 values increased further at post-slaughter, which is evidence for nociception. Other groups showed decreased post-slaughter F50, indicating increased pain threshold. Based on histological findings, the highest prefrontal cortex (PFC) pyramidal cells c-Fos activities were in the T2-L6 goats. Together with increased serum CK from muscle damage, this manifestation is suggested to be associated with aggressive behaviour among goats. Increased PFC c-Fos activities in T6-L6 goats suggest involvement of SIA that had increased pain threshold. Increased EEG δ and θ power at post-slaughter indicate state of unconsciousness, which is proposed to also occur via the SIA mechanism. Based on the findings from the study, it is recommended that the length of lairage period after 2- and 6-h transportation should be between 6 to 16 h when aggressive physical interactions had reduced, for animals to experience minimal slaughter pain. The study showed that there is a relationship between activation of pyramidal cells c-Fos expression in the PFC of goats and the EEG responses to the stress and pain of slaughter. In conclusion, it is elucidated that emotional and cognitive elements of goats at pre-slaughter can affect stress regulation and influence the slaughter pain response in goats through the SIA mechanism.